PRANDTL'S SURFACE MAXIMUM'S SPLIT FOR THE INTERSECTIONS WITH ISTHMUSES - Сеничак, Василь Михайлович; Ріпецький, Роман Йосипович; Сеничак, Владислав Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The thesis presents a research and computer analysis for the bifurcation phenomenon of the Prandtl's stress surface's maximum for the rounded and square rods with circular rifling of variable radius.